2023
DOI: 10.3390/ijerph20105788
|View full text |Cite
|
Sign up to set email alerts
|

Dribble Accuracy and Arm Coordination Pattern According to Motor Expertise and Tempo

Abstract: Skilled movements in motor learning result from efficiently controlling the many degrees of freedom in human movement. To acquire motor skills, harmonious coordination of body segments in time and space is crucial for accurate and consistent performance. The purpose of this study was to compare dribbling accuracy, consistency, and coordination patterns of body segments according to motor expertise and tempo. To achieve this, we had eight basketball experts and eight beginners perform static dribbling at three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…As 8–to 9-year-olds refine their hand-eye coordination, they gain the ability to perform complex movements with greater accuracy and fluidity. This improvement is due to the continued refinement of neural pathways that facilitate communication between the brain and muscles ( Demers and Levin, 2017 ; Urai et al, 2022 ; Park and Jeong, 2023 ). As a result, 8–to 9-year-olds can engage in activities that require intricate hand-eye and motor coordination, such as dance, team sports, and various forms of artistic expression ( Ludyga et al, 2022 ; Pastorek Gripson et al, 2022 ; Tao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…As 8–to 9-year-olds refine their hand-eye coordination, they gain the ability to perform complex movements with greater accuracy and fluidity. This improvement is due to the continued refinement of neural pathways that facilitate communication between the brain and muscles ( Demers and Levin, 2017 ; Urai et al, 2022 ; Park and Jeong, 2023 ). As a result, 8–to 9-year-olds can engage in activities that require intricate hand-eye and motor coordination, such as dance, team sports, and various forms of artistic expression ( Ludyga et al, 2022 ; Pastorek Gripson et al, 2022 ; Tao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…To succeed on the court, players need to be skilled at passing, dribbling, shooting, and defensive positioning, which are essential for a productive game. Basketball players with more experience demonstrated an in-phase coordination pattern and more consistency in their dribbling precision, whereas novice players displayed an anti-phase structure (Park & Jeong, 2023). Basketball players of various levels and positions have varying motor skills, such as running speed, explosive strength, and direction-changing speed (Stankovic et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Athletic performance in basketball is determined by the level of development of coordination and reaction time, components of motor ability that are essential for optimizing technical execution [ 15 , 16 ]. Research has shown that a level of motor ability development, especially coordination, directly and significantly influences the performance level of basketball players, particularly in the junior categories [ 16 , 17 , 18 ]. The effectiveness of a basketball player in the training process and during matches depends on the level of physical, technical, and tactical preparation in relation to the trends of dynamizing the game and the modernizing of specific training methodologies [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%